The impact of online educational modules on learning musculoskeletal anatomy for health professionals. A systematic review - Nikita Bandekar; K.G. Mohandas Rao; Aithal P. Ashwini; K. Anniesmitha; Bincy M. George (Translational Research in Anatomy)
Background: Musculoskeletal (MSK) anatomy is fundamental to clinical practice in various healthcare disciplines, including medicine, physiotherapy, and orthopedics. Advancements in technology have led to an increased focus on online learning tools, providing alternatives to traditional teaching methods. Objective: This systematic review assesses the impact of online learning (e-learning) modules on musculoskeletal anatomy education among health professionals. Methods: A comprehensive search was conducted across Scopus, PubMed, Cochrane, Web of Science, and CINAHL. The eligibility criteria included studies involving health professionals and students in anatomy education using online learning interventions such as video lectures, 3D models, and virtual labs. The risk of bias of the studies was evaluated via the JBI Checklist. Results: Out of 947 records, 18 studies were included in this review. This review included 8 quasi experimental, 7 cross-sectional, 1 case‒control, and 2 randomized controlled trials (RCTs). A total of 78 % of the studies incorporated multiple online interventions, such as video tutorials, interactive 3D models, and virtual laboratories. Additionally, 67 % of the studies indicated that learners preferred hybrid models that combined online and in-person teaching, as they significantly enhanced the learning experience compared with traditional methods in improving anatomical knowledge and musculoskeletal competency. Modules that incorporated practical elements significantly increased learners’ confidence in handling musculoskeletal cases. The pandemic accelerated the adoption of online anatomy education, with many studies demonstrating that digital platforms successfully replaced traditional methods while achieving comparable educational outcomes. Conclusions: Online educational modules offer a beneficial alternative to traditional anatomy teaching methods, particularly when interactive and hybrid models are in use. They enhance MSK knowledge retention, clinical skills, and learner satisfaction. Future studies should aim to optimize these technologies to integrate theoretical knowledge with clinical practices and patient education.